2014
DOI: 10.1093/jisesa/ieu032
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression Analysis of Four Heat Shock Protein Genes in Ericerus pela (Homoptera: Coccidae)

Abstract: To explore the function of small heat shock protein genes ( shsp s) and hsp70 in Ericerus pela , we cloned the full-length cDNA sequences of hsp21.5 , hsp21.7 , hsp70 , and hsc70 and the genomic sequence of hsc70 . Open reading frames of the four hsp s were 570, 564, 1,908, and 1,962 base pairs (bp), respectively, which encode proteins with calculated molecular mass of 21.5, 21.7, 69.8, and 71.6 kDa. Amino acid sequence analysis revealed the presence of the conserved Hsp motifs in all four proteins. The genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…In addition, genome-wide analysis while explicit the presence of 16 HSPs in the embryo of B. mori [23], the mRNA level as a fact of gene expression measured quantitatively was not correlated with the amount of HSPs synthesized [24] where they facilitate embryo development and metabolism by ensuing proteins properly folded and protecting against their denaturation [15] as reported in the present study. Augmenting, the expression of HSPs measured in larval and adult stages was also found higher than the egg stage of Ericerus pela [22] and HS in Drosophila eggs did not induce HSPs in early developmental stages [19]. The molecular mechanism in differential expression of HSPs in different developmental stages in the life cycle of any insects still remains obscure but shall be correlated with sensitivity of the embryo to a HS that lead to low hatchability as recorded in the present study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, genome-wide analysis while explicit the presence of 16 HSPs in the embryo of B. mori [23], the mRNA level as a fact of gene expression measured quantitatively was not correlated with the amount of HSPs synthesized [24] where they facilitate embryo development and metabolism by ensuing proteins properly folded and protecting against their denaturation [15] as reported in the present study. Augmenting, the expression of HSPs measured in larval and adult stages was also found higher than the egg stage of Ericerus pela [22] and HS in Drosophila eggs did not induce HSPs in early developmental stages [19]. The molecular mechanism in differential expression of HSPs in different developmental stages in the life cycle of any insects still remains obscure but shall be correlated with sensitivity of the embryo to a HS that lead to low hatchability as recorded in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, the expression of HSPs was not so obvious at the embryonic stage unlike larval stage of B. mori [14,21], while presence of nine HSPs was identified thorough shotgun proteomic analysis [15] which are known to involve in the basic metabolic process, but are not inducible in due to environmental stresses [22]. In addition, genome-wide analysis while explicit the presence of 16 HSPs in the embryo of B. mori [23], the mRNA level as a fact of gene expression measured quantitatively was not correlated with the amount of HSPs synthesized [24] where they facilitate embryo development and metabolism by ensuing proteins properly folded and protecting against their denaturation [15] as reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies revealed that the expression patterns of the orthologous shsps among different organisms are not exactly the same, which is probably related to their different physiological characteristics. In E. pela , a species highly sexually dimorphic with holometamorphic males and hemimetabolic females, the mRNA levels of Ephsp21.5 showed the lowest expression in eggs, and in males it was maximal in adults stage and in females it reached a maximum in second‐stage larvae (Liu et al., ). This phenomenon is due to that the female insects enter the adult stage in August (hot weather), whereas the male larvae continuously keep in the second‐instar stage.…”
Section: Discussionmentioning
confidence: 99%
“…These insects have been bred in China for over a thousand years. E. pela is widely distributed in China, the Korean Peninsula and Japan (Yang et al ., , , ; Liu et al ., ). E. pela can even survive and produce offspring in the Jilin and Xizang Provinces in China, where the lowest temperature is below ‐30°C.…”
Section: Introductionmentioning
confidence: 97%